Level of Integrity, Availability teachers, implementation of school-based assessment, Teaching Profession - Mohamad Nizam Bin Nazarudin; Norsyamsiah Binti Waridi; Ismail Bin Saad (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The purpose of this study is to study the impact of agility training programs on the improvement of motor skills-based fitness components among control and treatment groups. A total of 32 novice rugby novels from the Show Rugby Club were randomly divided into control groups (N = 16) and treatment group (N = 16). The treatment group had undergone reactive agility training program for 8 weeks while the control group undergoes traditional training. Statistical data analysis uses paired t - test and ANOVA repetitive measurements. The findings show that there is a difference in the effect of reactive agility training and traditional agility training on motor-based fitness components. There is a significant difference in the mean score of speed test, agility, balance and reaction time p = <.05 between treatment groups and control groups. There was no significant difference p => .05, for the coordination and control tests between control and treatment groups. The treatment group has shown a better improvement compared to the control group. This proves that reactive dexterity training using i - Agile system software has improved the physical fitness component based on motorists among novice rugby players better than traditional training methods. Teen novels rugby trainers need to change to the use of reactive agility training in their training sessions. There is a need now to make more innovations and further studies on reactive agility training in the future.